2020
DOI: 10.3390/children7090103
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Cognitive Dysfunction in Children with Neurologically Stable Opsoclonus–Myoclonus Syndrome

Abstract: Cognitive and acquired neurodevelopmental deficits have been reported in children with opsoclonus–myoclonus syndrome (OMS) and are known to be associated with more severe and relapsing disease course. However, there is a paucity of data regarding cognitive dysfunction in children with stable neurological disease. We report three children with OMS and evolving cognitive dysfunction in the context of a mild disease course. The children’s ages at disease onset were between 17 and 35 months and they were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…We found that the DQ of patients at the last follow-up was 77.6 ± 9.8. And three OMS patients in En Lin et al's study had evolving cognitive dysfunction despite being in remission and been followed up for a long time (ranged from 5 to 10 years) (38). In our study, we found the DQ of patients at the last follow-up was not correlated with the age at onset, the OMS severity score onset or last follow-up, the number of relapses, the duration of follow-up.…”
Section: Discussioncontrasting
confidence: 45%
“…We found that the DQ of patients at the last follow-up was 77.6 ± 9.8. And three OMS patients in En Lin et al's study had evolving cognitive dysfunction despite being in remission and been followed up for a long time (ranged from 5 to 10 years) (38). In our study, we found the DQ of patients at the last follow-up was not correlated with the age at onset, the OMS severity score onset or last follow-up, the number of relapses, the duration of follow-up.…”
Section: Discussioncontrasting
confidence: 45%
“…One series of 3 patients described progressive cognitive dysfunction despite a stable clinical course following treatment. 59 …”
Section: The Long-term Outcome and Management Of Omasmentioning
confidence: 99%
“…One series of 3 patients described progressive cognitive dysfunction despite a stable clinical course following treatment. 59 Given the significant symptoms and impact on development, treatment is targeted at inducing full remission, tolerating no symptoms, and acting promptly to avoid or mitigate relapses. Ongoing physical, occupational, and speech therapy should be recommended for all patients with OMAS, although many children will not tolerate therapies early in the course due to irritability.…”
Section: The Long-term Outcome and Management Of Omasmentioning
confidence: 99%
“…They also reported that the risk factors for neurological sequelae were the female sex, a residual tumor, and a non-adrenal-gland-located tumor [ 90 ]. Goh et al followed three children with OMAS from 4 to 10 years of age and reported that significant deficits in attention, processing speed, visuospatial skills, and language were observed in the long term [ 91 ]. In 2011, Brunklaus et al concluded, from a retrospective review of 101 patients with OMAS over a 53-year period, that 60% of the patients had residual motor problems, while 66% had speech abnormalities, 51% had learning disabilities, and 46% had behavioral problems.…”
Section: Reviewmentioning
confidence: 99%